(3OjhGf GdTGH GdXQjas - (3GdTGH GdXQja , CHhYHO Gddg eMeO Hf SdjeGf Hf Ydj Hf YHO Gddg GdJdeSGfj, GdTGH GdXQja,J (B688 (3g` s
(3ChdgG (B:s
(3bGajI GdgeRI bGd GdTGH GdXQja jhe CJGfG HQOg aj HQOg CVMi HgG eKd GdMOjO GdeGoA s
(3BNQgG (B:s
(3hHrSbe GdfGXQjf cSi Lafc GdSeGQ aGfcSQG s
(3Ydi GdfSNI Jedc SfI (B997(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B150 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B53s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B125 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B767s
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(2/382) s
Keywords: (3GdCOHs